(untitled) (Physical Education, Health and Social Sciences, 2025)
Hepatocellular carcinoma (HCC) is a major health issue worldwide, rating as the 6th most common malignancy and a number one motive of most cancers-associated mortality worldwide. Chronic exposure to Hepatitis B (HBV) and Hepatitis C (HCV) viruses remains an important danger thing. We analyzed clinical data of two hundred (200) HCC patients who were visiting the Outpatient Department (OPD) and those who were admitted in oncology ward at Allied Hospital, Faisalabad. A total of a hundred and sixty (160) males and forty (40) females included in this study. Hepatocellular carcinoma is high risk factor for men as compared to women on account of hormones variation as depicted in the study. Demographic analysis, approximately 60 percent of HCC development occurred among patients aged 40 to 50 years. Etiological assessment indicated an extensively higher occurrence of HCV-associated HCC, with 145 patients having chronic HCV as compared to 55 patients with HBV-related carcinoma. The clinical assessment on the time of evaluation revealed that 18 out of the 200 patients were having metastatic disorder. A vital statement becomes that 60% of the patients have been recognized with HCC prior to being aware of their underlying viral contamination, highlighting an alarming defect in early detection and disease awareness. These results highlight the high prevalence of HCV-related HCC in the population and the severe negative effect of late-stage presentation on patient survival. To mitigate these risks, there is a pressing need for systematic screening for metastasis in HCC patients, significant surveillance for hepatitis viruses inside high-hazard populations, and more suitable public focus. Furthermore, powerful healing control of HBV and HCV infections is critical to lessen the development of carcinoma and improve survival rate. Key Words: HCC, HCV, HBV, Metastatic